Analysing the Impact of Self-Efficacy on Employee Performance: The Mediating Role of Work Motivation at Permodalan Nasional Madani, Majalengka Branch 2 - Hazizah, Sella; Hartati, Wiwi; Risdianto, Risdianto (Politeknik Negeri Ambon, 2025)
Introduction: In the era of increasingly dynamic business competition, employee performance is greatly influenced by psychological factors, including self-efficacy, or the individual's belief in their ability to complete tasks. This study aims to analyze the influence of self-efficacy on employee performance with work motivation as an intervening variable at Permodalan Nasional Madani (PNM) Branch Majalengka 2.Methods: This quantitative research employed the saturated sampling method, administering questionnaires to 50 PNM employees. The Sobel test and multiple regression were used to assess the variables' direct and indirect effects on the data.Results: The research results show that self-efficacy positively and significantly impacts worker performance and their motivation to work. Furthermore, the main finding of this study is that work motivation significantly mediates the relationship between self-efficacy and work motivation.Conclusion and Suggestion: This Research demonstrates that self-efficacy positively and significantly impacts work motivation and employee performance. Employees with high confidence in their abilities tend to be more motivated, leading to improved performance. Work motivation also proves to mediate the relationship between self-efficacy and performance, meaning that high self-efficacy will encourage strong work motivation, ultimately improving employee performance. Therefore, companies should be able to enhance employee self-efficacy through training, coaching, and psychological support to support sustainable performance improvement. Keywords: Self-efficacy, Employee Performance, and Work Motivation